The Notions of Local and Global Culture in the Contemporary Urban Society : 'Melting Pot' and 'Salad Bowl' : Concepts taken together? - Čaldarović, Ognjen (2008)
Concepts of "melting pot" and "salad bowl" are taken within the perspective of globalization. A central thesis of the paper is that both concepts must be combined in order to explain contemporary urban phenomenons that are developing in major urban centers in the world.